Upaya Peningkatan Keamanan Obat Diabetes Mellitus di Klinik Pratama Swasta dengan Pendekatan Action Research - Merita Arini; Ikrima Khaerun Nisa; Harumi Iring Primastuti (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Medication safety is one of the patient safety criteria that must be met in healthcare facilities. However, research on medication safety in private primary care remains limited. This study aimed to increase medication safety initiatives for Diabetes Mellitus (DM) patients and healthcare recipients’ (patients') knowledge of medication safety. A cycle of action research (diagnosing, planning, action, and evaluation) was used in a private clinic (PKU Muhammadiyah Srandakan Clinic, Yogyakarta Special Region). The involvement level of research subjects was co-learning. The diagnosing phase was conducted by in-depth interviews and questionnaires distribution with clinical leaders and staff (n=11). The planning stage was completed through medication prescription standard operational (SPO) procedure review and the educational media preparation for patients. In the action stage, in-house training for clinic staff about medication safety and the educational intervention with a quasi-experimental (without control, non-randomization) on PROLANIS DM participants (total sampling, n=50) were conducted. Study results showed that the diagnosing phase exposes the clinic staff's adequate understanding of medication safety. There were obstacles to implementing prescribing services from the patient, staff, operational, and infrastructure aspects. A revised SPO for Prescription Medication Services and educational media were created during the planning stage. There was a significant increase in patients’ knowledge between the pre-test and post-test in the action and evaluation stage (p=0.000), and there was no patient safety incident related to medication safety during this research. In conclusion, staff knowledge was good, there was a significant increase after health education was provided to patients, and complex obstacles need to be resolved comprehensively and continuously.